The Effect of Family Disruption on Children's Personality Development: Evidence from British Longitudinal Data - Tyas Prevoo; Bas ter Weel (Institute for the Study of Labor (IZA), 2014)
This research documents the effects of different forms of family disruptions measured by separation, divorce and death on personality development of British children included in the 1970 British Cohort Study. There are statistically significant correlations between family disruptions prior to the age of 16 and personality development in early childhood. Parental divorce has the largest negative effect on a child's personality development. Family disruptions have smaller effects on personality development when children are older and patterns differ by gender. The relationship between personality development and family disruption is partially driven by selection. Placebo regressions reveal significant correlations between family disruption and personality development before disruption. The omitted variable bias is mitigated by investigating mechanisms through which the selection operates.
Keywords: J12; J24; 330; family disruption; personality development